2002
DOI: 10.1161/01.cir.0000047200.36165.b8
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transcatheter Implantation of an Aortic Valve Prosthesis for Calcific Aortic Stenosis

Abstract: Background-The design of a percutaneous implantable prosthetic heart valve has become an important area for investigation. A percutaneously implanted heart valve (PHV) composed of 3 bovine pericardial leaflets mounted within a balloon-expandable stent was developed. After ex vivo testing and animal implantation studies, the first human implantation was performed in a 57-year-old man with calcific aortic stenosis, cardiogenic shock, subacute leg ischemia, and other associated noncardiac diseases. Valve replacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
1,062
0
75

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,797 publications
(1,211 citation statements)
references
References 10 publications
6
1,062
0
75
Order By: Relevance
“…The first‐in‐man TAVI was performed in 2002 by Alain Cribier in France 7. Ever since excellent achievements have been made in the field of TAVI saving lots of lives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first‐in‐man TAVI was performed in 2002 by Alain Cribier in France 7. Ever since excellent achievements have been made in the field of TAVI saving lots of lives.…”
Section: Discussionmentioning
confidence: 99%
“…Ever since excellent achievements have been made in the field of TAVI saving lots of lives. The PARTNER trials comparing TAVI with SAVR in high‐risk severe aortic stenosis patients were the cornerstone for TAVI, which showed similar survival rates at 1 year,8 improved valve hemodynamic at 2 years, reduction in symptoms, death rates, and hospitalizations 7, 9. TAVI, however, showed more frequent paravalvular regurgitation and increased late mortality 7, 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since transcatheter valve implantation (TVI) was carried out for the first time in 2002 [22], its technology has been developing speedily. TVI is less-invasive treatment than valve surgery and more patients with a high-risk for valve surgery have been undergoing TVI.…”
Section: Beforementioning
confidence: 99%
“…5,6 Percutaneous approaches to AV replacement have been investigated since 1992. 7 in 2002, Cribier et al 8 reported a successful percutaneous valve replacement via an antegrade transseptal approach through the femoral vein. However, due to arrhythmias and possible mitral valve injury, the antegrade approach is technically challenging and not well tolerated by some patients.…”
Section: éLéments Cliniques : Une Fois Le Consentement Du Comité D'étmentioning
confidence: 99%